Daily Rice Bran Consumption for 6 Months Influences Serum Glucagon-Like Peptide 2 and Metabolite Profiles without Differences in Trace Elements and Heavy Metals in Weaning Nicaraguan Infants at 12 Months of Age. Issue 9 (21st July 2021) - Zambrana, Luis E; Weber, Annika M; Borresen, Erica C; Zarei, Iman; Perez, Johann; Perez, Claudia; Rodríguez, Iker; Becker-Dreps, Sylvia; Yuan, Lijuan; Vilchez, Samuel; Ryan, Elizabeth P
ABSTRACT: Background: Environmental enteric dysfunction (EED) is associated with chronic gut inflammation affecting nutrient absorption and development of children, primarily in low- and middle-income countries. Several studies have shown that rice bran (RB) supplementation provides nutrients and modulates gut inflammation, which may reduce risk for undernutrition. Objective: The aim was to evaluate the effect of daily RB dietary supplementation for 6 mo on serum biomarkers in weaning infants and associated changes in serum and stool metabolites. Methods: A 6-mo randomized-controlled dietary intervention was conducted in a cohort of weaning 6-mo-old infants in León, Nicaragua. Anthropometric indices were obtained at 6, 8, and 12 mo. Serum and stool ionomics and metabolomics were completed at the end of the 6-mo intervention using inductively coupled plasma MS and ultra-high performance LC–tandem MS. The ɑ1-acid glycoprotein, C-reactive protein, and glucagon-like peptide 2 (GLP-2) serum EED biomarkers were measured by ELISA. Results: Twenty-four infants in the control group and 23 in the RB group successfully completed the 6-mo dietary intervention with 90% dietary compliance. RB participants had higher concentrations of GLP-2 as compared with control participants at 12 mo [median (IQR): 743.53 (380.54) pg/mL vs. 592.50 (223.59) pg/mL; P  = 0.04]. Metabolite profiles showed significant fold differences of 39 serum metabolites and 44 stool metabolites from infants consuming RB compared with control, and with significant metabolic pathway enrichment scores of 4.7 for the tryptophan metabolic pathway, 5.7 for polyamine metabolism, and 5.7 for the fatty acid/acylcholine metabolic pathway in the RB group. No differences were detected in serum and stool trace elements or heavy metals following daily RB intake for 6 mo. Conclusions: RB consumption influences a suite of metabolites associated with growth promotion and development, while also supporting nutrient absorption as measured by changes in serum GLP-2 in Nicaraguan infants. This clinical trial was registered at https://clinicaltrials.gov as NCT02615886. Abstract : Rice bran modulates glucagon-like peptide 2, serum, and stool metabolites in weaning Nicaraguan infants.